Endurance limit of aluminum, brass and mild steel on different surface finish owing to cyclic loads - Ahmad Fitri, Zainal Abidin (2009)
The investigation is about the endurance limit of aluminum, brass and mild steel that has been done at the surface of the specimens on different surface roughness. The endurance limit of the specimens have been determined by testing under different loads on the fatigue testing machine and the life cycles of each specimens has been taken after crack occur on the specimen. Endurance limit is defined as the alternating stress that causes failures after some specified number of cycles. This study or investigation has the steps that is starting form the fabrication on different surface roughness, testing on the fatigue machine and gather all the data to compare the results.. The different surface roughness will give different life cycles. Then, comparison of the result needs to be done to get the best materials on different surface roughness to create a good choosing of materials in industry. Finally, studies of Endurance limit or fatigue strength can still be expanded and widened due to the other properties that can be tested such as curvature radii and elongation of the materials due to a break point.